Sacred Conversation: A Spiritual Response to Unavoidable Suffering - Couture, Shari (Canadian Journal of Counselling and Psychotherapy, 2007)
Pain and tragedy beset human beings in many ways during their lives. The death of a loved one, infidelity, divorce, or chronic illness are among the experiences that can result in overwhelming suffering. Existential psychiatrist Victor Frankl believed that transcendent meaning could be found even in such dark and desperate moments. It is often during times of suffering that profound and deeply personal questions about meaning and purpose in life may arise. These questions are at the very heart of spiritual concerns. The authors believe such questions can be explored in the therapeutic context in order to help the client gain a sense of meaning in their suffering, as well as a measure of peace in their lives. The authors' approach, entitled Sacred Conversation, uses Frankl's work as well as literature on empathy, forgiveness, and spirituality as its foundation.